Metabotropic Glutamate Receptors 1 Regulates Rat Carotid Body Response to Acute Hypoxia via Presynaptic Mechanism - Li, Chaohong; Zhao, Baosheng; Zhao, Chenlu; Huang, Lu; Liu, Yuzhen (Frontiers in Neuroscience, 2021)
Background: The carotid body (CB) plays a critical role in oxygen sensing; however, the role of glutamatergic signaling in the CB response to hypoxia remains uncertain. We previously found that functional multiple glutamate transporters and inotropic glutamate receptors (iGluRs) are expressed in the CB. The aim of this present research is to investigate the expression of group I metabotropic glutamate receptors (mGluRs) (mGluR1 and 5) in the CB and its physiological function in rat CB response to acute hypoxia. Methods: RT-PCR and immunostaining were conducted to examine the mRNA and protein expression of group I mGluRs in the human and rat CB. Immunofluorescence staining was performed to examine the cellular localization of mGluR1 in the rat CB. In vitro carotid sinus nerve (CSN) discharge recording was performed to detect the physiological function of mGluR1 in CB response to acute hypoxia. Results: We found that: 1) mRNAs of mGluR1 and 5 were both expressed in the human and rat CB. 2) mGluR1 protein rather than mGluR5 protein was present in rat CB. 3) mGluR1 was distributed in type I cells of rat CB. 4) Activation of mGluR1 inhibited the hypoxia-induced enhancement of CSN activity (CSNA), as well as prolonged the latency time of CB response to hypoxia. 5) The inhibitory effect of mGluR1 activation on the CB response to hypoxia could be blocked by GABAB receptor antagonist. Conclusions: Our findings reveal that mGluR1 in CB plays a presynaptic feedback inhibition on rat CB response to hypoxia.